2012
DOI: 10.1152/jn.00516.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cortical stimulation causes long-term changes in H-reflexes and spinal motoneuron GABA receptors

Abstract: The cortex gradually modifies the spinal cord during development, throughout later life, and in response to trauma or disease. The mechanisms of this essential function are not well understood. In this study, weak electrical stimulation of rat sensorimotor cortex increased the soleus H-reflex, increased the numbers and sizes of GABAergic spinal interneurons and GABAergic terminals on soleus motoneurons, and decreased GABA A and GABA B receptor labeling in these motoneurons. Several months after the stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
(101 reference statements)
0
12
1
Order By: Relevance
“…In the chronic spinal cat, studies have shown that training could act on the central pattern generator (CPG) excitability by modulating spinal cord inhibitory circuits (de Leon et al 1999). In addition, training might induce changes in the firing threshold and conduction velocity of motoneurons [mechanisms explored in a series of studies on monosynaptic stretch reflex, which can be modulated in both animals and humans (Wang et al 2012;Wolpaw 1997)] that might be crucial in the adaptation of the CPG excitability. Finally, neuromodulators such as monoamines or neuropeptides can influence the functional status of the CPG circuitry (Ribotta et al 2000).…”
Section: Mechanisms Of Activity-dependent Plasticity Within Spinal Nementioning
confidence: 99%
See 1 more Smart Citation
“…In the chronic spinal cat, studies have shown that training could act on the central pattern generator (CPG) excitability by modulating spinal cord inhibitory circuits (de Leon et al 1999). In addition, training might induce changes in the firing threshold and conduction velocity of motoneurons [mechanisms explored in a series of studies on monosynaptic stretch reflex, which can be modulated in both animals and humans (Wang et al 2012;Wolpaw 1997)] that might be crucial in the adaptation of the CPG excitability. Finally, neuromodulators such as monoamines or neuropeptides can influence the functional status of the CPG circuitry (Ribotta et al 2000).…”
Section: Mechanisms Of Activity-dependent Plasticity Within Spinal Nementioning
confidence: 99%
“…In addition, although a larger amount of spared inputs is generally associated with a better recovery, few studies have demonstrated a negative role of preserving a larger amount of tissue on locomotor recovery and/or spinal plasticity. It has been shown that in health and disease, descending inputs are involved in shaping and remodeling the spinal cord (Chen et al , 2006(Chen et al , 2007Wang et al 2012) and probably play a beneficial role in locomotor recovery (Thomas and Gorassini 2005) by allowing the spinal circuitry to remain in an active state after iSCI. By contrast, some studies have also reported that the disruption of some supraspinal pathways after SCI could lead to maladaptive plasticity in spinal sensory (Ferguson et al 2012) and reflex pathways (Tan et al 2012), but to our knowledge, none of these studies have shown a correlation between the number of spared pathways and the occurrence of maladaptive events.…”
mentioning
confidence: 99%
“…The charge injection to evoke limb muscle response here was 2 nC which is low when compared with screw electrodes (15 -200 nC (Mishra et al, 2017, Wang et al, 2012 and surface placed wires (180 nC (Carmel et al, 2014)). When compared with MEMS fabricated electrodes, there was comparable charge injection albeit at a lower spatial resolution; surface electrodes (2.13 nC (Molina-Luna et al, 2007)) and intracortical needle electrodes (15 nC (Wang et al, 2013)).…”
Section: Resultsmentioning
confidence: 70%
“…Studies in rats and non-human primates indicate that the smaller H-reflex produced by steady-state conditioning is largely attributable to a positive shift in motoneuron firing threshold (Carp & Wolpaw, 1994); it is associated with increases in GABAergic input to the motoneuron (Wang et al 2006;Wang et al 2012) and in the number of GABAergic interneurons in the ventral horn (Wang et al 2009). The present finding that swing-phase conditioning also decreases the standing H-reflex ( Fig.…”
Section: Mechanisms Of H-reflex Decrease With Swing-phase Conditioningmentioning
confidence: 99%